Roles of carbon nanotubes in reinforcing the interfacial transition zone and impermeability of concrete under different water-to-cement ratios. (22nd February 2021) - Gao, Yuan; Jing, Hongwen; Zhou, Zefu; Shi, Xinshuai; Li, Luan; Fu, Guangping
Highlights: CNTs reinforce the ITZ characteristics and anti-permeability of concrete. Either higher or lower W/C ratios may impair the reinforcing effects of CNTs. CNTs assist hydrated products growth in ITZ during the hydration of concrete. CNTs form net-like distributions and inhibit flaws propagation in hardened ITZ. Abstract: Concrete plays a central role in fundamental construction and engineering. However, the interfacial transition zone (ITZ), as the area between the aggregates and cementitious pastes, is the weakest component in concrete and always limits the properties and application of the concrete. Here, we reveal the potential of carbon nanotubes (CNTs) as superior additives for reinforcing the ITZ in concrete and the corresponding impermeability enhancement against various of water-to-cement (W/C) ratios. The results suggest that CNTs not only promote higher hydration reaction and generate more hydrated products to dense ITZ area, but also form net-like distributions to inhibit flaws propagation at the microscale. Compared with the plain concrete specimens, the addition CNTs micrified the ITZ width by 14.3–30% and reduced the abrasion crack width by 19.5–35%. The reinforcing effects of CNTs on ITZ characteristics are consistent with Gauss fitting and achieve the highest enhancement at 0.4 W/C ratio. The corresponding impermeability properties of concrete present a linear correlation with both ITZ width and abrasion crack width, which can be strengthened by approximately 10.9%-35.8% assisted by CNTs. Furthermore, selecting the appropriate W/C ratios is the key to make full use of CNTs roles in strengthening the ITZ of concrete. High W/C ratios may lead to the re-agglomeration of CNTs and low W/C ratios would promote CNTs to act as pulled-out roles and weaken their ability to inhibit flaws propagation.